The Flow Cytometric Analysis of Peripheral Blood Lymphocytes and Expression of HLA II Molecules in Lymphocyte During Acute Rejection After Renal Transplantation - Guo J; Qin C; Li X; Zhuang X (Dove Medical Press, 2023)
Jianzhuang Guo,1 Chengwei Qin,2 Xiangdong Li,1 Xiaoxuan Zhuang3 1Department of Clinical Laboratory, The First Affiliated Hospital of Shandong First Medical University (Shandong Provincial Qianfoshan Hospital), Jinan, Shandong, People's Republic of China; 2Department of Anesthesiology, Shandong Second Provincial General Hospital, Jinan, Shandong, People's Republic of China; 3International Medical College of Chongqing Medical University, Chongqing, People's Republic of ChinaCorrespondence: Xiangdong Li; Chengwei Qin, Email lixd03@21cn.com; qinchengweiqcw8k@126.comObjective: To investigate the changes in the proportion of peripheral blood lymphocytes and the expression of HLA II molecules in lymphocytes during acute rejection after renal transplantation.Methods: Thirty-five patients who had undergone renal transplantation were selected. Eighteen patients with clinical and pathological confirmed acute rejection were selected as the test group, and twelve patients without clinical acute rejection symptoms were selected as the control group. Flow cytometry analysis was used to determine the proportion of peripheral blood lymphocytes. The mRNA and protein expression of HLA II molecules on peripheral blood lymphocytes were detected using real-time fluorescence quantification and immunoblotting, respectively.Results: The proportion of T lymphocytes, B lymphocytes, and CD4CD8 double positive T cells in the Control Group were 67.48% ± 5.35%, 10.82% ± 1.26%, and 0.88% ± 0.06%, respectively, and in the Test Group were 87.52% ± 6.28%, 3.36% ± 0.26%, and 0.34% ± 0.03%, with a significant difference respectively. The mRNA and protein expressions of HLA II molecules of peripheral blood B lymphocytes in the control group were significantly higher that these in the test group.Conclusion: The proportion of peripheral blood T lymphocytes, B lymphocytes, CD4CD8 double positive T cells, and the expression of HLA II molecules of peripheral blood lymphocytes can all indicate the occurrence of acute renal transplantation rejection, which were exceedingly useful to clinicians in judging the acute rejection of renal transplantation in the early stages.Keywords: acute rejection, HLA II molecules, kidney transplantation, peripheral blood lymphocytes, flow cytometric analysis